Synthesis of 1-[1-(diphenoxyphosphoryl)alkyl]-3,4,6-trimethylglycolurils - Gorbin, Sergey I.; Bakibaev, Abdigali A.; Kurgachev, Dmitryi A.; Malkov, Victor S.; Novolokov, Kirill Yu; Sysoev, Gleb O. (Mendeleev communications)
The reaction of 1,3,4-trimethylglycoluril, aliphatic aldehydes and triphenyl phosphite in the presence of methanesulfonic acid affords new phosphorus-containing derivatives of glycoluril. The thus formed diastereomers of 1-[1-(diphenoxyphosphoryl)alkyl]-3,4,6-trimethylglycolurils were separated by reverse-phase HPLC.